1991
DOI: 10.1007/bf02536067
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid composition of brain phospholipids in aging and in Alzheimer’s disease

Abstract: The two major phospholipid classes, namely, phosphatidylethanolamines (PE) and phosphatidylcholines (PC), were studied in four different regions of human brain, i.e., in frontal gray matter, frontal white matter, hippocampus and in pons. The fatty acid (FA) compositions of these phospholipids were found to be specific for the different regions. PC contains mostly saturated and 18:1 FA, while PE is rich in polyunsaturated FA. Aging has no influence on the FA compositions, while in Alzheimer's disease (AD) PE is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

25
412
4
17

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 606 publications
(458 citation statements)
references
References 20 publications
25
412
4
17
Order By: Relevance
“…The membrane phospholipids in brain contain high concentrations of the LCPUFA docosahexaenoic acid (DHA) [5], with highest levels observed in synaptic membranes [6,7], the growth cones of neurites [8,9] and rod outer segments of the retina [10,11]. Clinical and laboratory studies indicate that a number of neurodegenerative diseases involve cell membrane abnormalities which are associated with DHA deficiency [12][13][14][15], and that supplementation with DHA may offer protection against neuronal damage and cell death [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…The membrane phospholipids in brain contain high concentrations of the LCPUFA docosahexaenoic acid (DHA) [5], with highest levels observed in synaptic membranes [6,7], the growth cones of neurites [8,9] and rod outer segments of the retina [10,11]. Clinical and laboratory studies indicate that a number of neurodegenerative diseases involve cell membrane abnormalities which are associated with DHA deficiency [12][13][14][15], and that supplementation with DHA may offer protection against neuronal damage and cell death [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…It is present in neuronal tissue, nerve terminals and synapses, predominantly within membrane phospholipid constituents phosphatidylethanolamine, phosphatidylserine, and phosphatidylcholine (Martin and Bazan 1992;Martin et al 1994). Of the total fatty acid content in brain regions, DHA constitutes approximately 22% in frontal cerebral cortical gray matter, 16% in hippocampus, and in lower proportions in white matter and in some subcortical regions (Söderberg et al 1991). Brain is virtually entirely dependent on intake of exogenous, and mainly dietary, DHA (Innis 1991).…”
mentioning
confidence: 99%
“…The evidence has demonstrated that during the embryonic stage and the first years of life, DHA plays a key role in the growth and development of the nervous and visual systems, actively participating in the processes of neurogenesis, neuronal migration, myelination and synaptogenesis (Uauy et al, 2001), thus directly impacting on cognitive development, visual, auditory, and in the memory and learning capabilities (McNamara & Carlson, 2006). As result of these observations, it is now strongly recommended to increase the consumption DHA during the pregnancy and childhood, in order to ensure the proper development of the nervous and visual systems (Uauy et al,reduced, being even greater this decrease in the population that develops neurodegenerative diseases (Sodeberg et al, 1991). This significant reduction may be caused either, by a lower intake of the fatty acid or of its metabolic precursor and/or by an increased in the cellular utilization of DHA (Jicha & Markesbery, 2010).…”
Section: Dha and Brain Ageingmentioning
confidence: 99%
“…DHA plays a relevant role in the preservation of both the histology and physiology of the neuronal tissue as the individual ages, by preserving the nervous system functions among which memory and learning are the most remarkable (Lukiw & Bazan, 2008). Several epidemiological studies have strongly established that a higher intake of foods rich in DHA (fatty fish and/or nutritional supplements based on fish oils or microalgae) is highly correlated with a lower risk of developing neurodegenerative diseases (Kalminj et al, 2004;Kalmijn et al, 1997), which is also associated with a clinical history indicating that patients with neurodegenerative disease have significantly lower levels of DHA in plasma and brain (Tully et al, 2003;Sodeberg et al, 1991).…”
Section: Dha and Brain Ageingmentioning
confidence: 99%
See 1 more Smart Citation